Isolates and Enumeration of Bacteria on the Expanse of Peat Soil in the DAS Kampar Riau Sumatera - Irma, Wirdati; Gunawan, Totok; Suratman, Suratman (Fakultas Perikanan dan Kelautan Universitas Riau, 2019)
Land can be said to be fertile seen from Biological factors. One of the Biological factors determining soil fertility is the population of bacteria in the soil. The purpose of this study was to calculate the population and describe the bacterial morphology of the Kampar Riau Sumatera Watershed. The method used in the this study is the observation and Coloni Counter method. Peat soil sampling was carried out at 8 peat soil points along the Kampar Riau Sumatera Watershed. Isolates were carried out using agar nutrient media and were fertilized for 24-48 hours at 370C. Macroscopic and microscopic observations were carried out to determine bacterial morphology. This research result obtained 16 isolates from 8 sample locations. The highest number of bacterial populations in the village of Kuala Terusan was 51,55 x 104 CFU/Unit and the lowest was found in Meranti Village with 12,93 x 104. Identified bacterial morfoligical characteristics are irregular, round, round with embossed edges and threaded threads. Cell shape 2 which is stem and round the catalase test are all positive